2018
DOI: 10.1007/s00266-018-1096-z
|View full text |Cite
|
Sign up to set email alerts
|

Education on the Business of Plastic Surgery During Training: A Survey of Plastic Surgery Residents

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 6 publications
1
19
0
Order By: Relevance
“…This was mirrored by previous studies, as one survey reported that nearly 90% of plastic surgeon respondents stated that business principles are either "pretty important" or "very important" to being a doctor. [11][12][13] More specifically, within our analysis, coding and billing were ranked as the highest topic of importance for instruction. There have been efforts to educate plastic surgery residents on such concepts through a multifaceted approach, and these have conferred significantly increased rates of higher complexity evaluation and management coding based on improved documentation and billing awareness by residents.…”
Section: Discussionmentioning
confidence: 99%
“…This was mirrored by previous studies, as one survey reported that nearly 90% of plastic surgeon respondents stated that business principles are either "pretty important" or "very important" to being a doctor. [11][12][13] More specifically, within our analysis, coding and billing were ranked as the highest topic of importance for instruction. There have been efforts to educate plastic surgery residents on such concepts through a multifaceted approach, and these have conferred significantly increased rates of higher complexity evaluation and management coding based on improved documentation and billing awareness by residents.…”
Section: Discussionmentioning
confidence: 99%
“…However, health policy and advocacy education have traditionally been lacking within US graduate medical education, with most non-medical educational efforts focusing on business preparedness and practice management among residents and recent graduates across many medical specialties. [1][2][3][4] These gaps in health policy and advocacy education can leave trainees feeling frustrated and paralysed; while trainees feel it is essential for physicians to participate in advocacy efforts to shape health policy, their perceived ability to do so is curtailed by a lack of knowledge surrounding these areas. 5 6 Further, lack of health policy and advocacy awareness can also be detrimental to the quality and equity of patient care provided, prompting calls to address this critical training gap.…”
Section: Introductionmentioning
confidence: 99%
“…In the changing U.S. health care environment, physicians are required to perform a wider variety of tasks and have a deeper understanding of nonmedical topics, such as health policy and healthcare economics. Studies have shown a lack of familiarity with principles in health policy and practice management among residents and recent graduates across a number of medical specialties [1][2][3][4][5], prompting numerous proposals and calls to action to improve health policy education within graduate medical education [6][7][8][9][10][11]. Although studies have characterized business preparedness among dermatology trainees [12,13], efforts to understand and educate dermatology trainees about health policy reforms pertaining to dermatology practice have not been required or standardized across dermatology residency programs [14][15][16].…”
Section: Introductionmentioning
confidence: 99%